The effect of chitosan waxing on the shelf-life of lanzones (Lansium domesticum Correa) - Sanico, Lyra Gay Egido (2003.)
One way of extending the shelf-life of highly perishable fruits is the application of waxing.
Thesis (Undergraduate. Bachelor of Science in Food Technology) School of Technology, University of the Philippines in the Visayas.
Keywords: Chitosan waxing; Lanzones--Shelf-life.; Lansium domesticum correa